Analisa Mampu Redam Suara Komposit Polyester Berpenguat Serbuk Gergaji dan Fly Ash - Haris, Muh. Jufri; Salimin, Salimin; Imran, Al Ichlas (Teknik Mesin Universitas Halu Oleo, 2018)
This damper material will raise awareness of the importance of reducing noise and the importance of utulizing waste products as a material that can be economically. This study aims to determine and amalyze the ability to dampen the sound of polyester composit with sawdust and fly ash mixture to the frequency of 1200 Hz, 1400 Hz and 1600 Hz. This eksperimental study was conducted with three different compositionvariations. The materials used are polyester resin, sawdust and fly ash. The data obtained is measured using a sound level meter. The result of this study showed that the material at a 70:20:10% volume fractionobtained the highest sound absorption coefficient value of 0,38248 dB with a frequency of 1600 Hz and for the lowest absorption coefficient value 0,11687 DB at volume fraction 60:30:10% with frequency 1200 Hz. The higher the value of sound absorption coefficient, the better the quality of the soundproofing material.Key word: Composite, resin polyester, sawdust, fly ash and NAC.